Attitudes Toward Environmental Literacy: A Study of Early Childhood Education Teachers in District Mardan, Khyber Pakhtunkhwa - Rahman, Nazeer; Shams, Jahan Ara; Iqbal, Muhammad Zafar (Social Science Review Archives, 2025)
The aim of the study was to determine the environmental literacy of Early Childhood Education (ECE) teachers of District Mardan, Khyber Pakhtunkhwa with the special focus on the attitude component. Using a census sampling technique, the population of Total ECE teachers in Tehsil Takht Bhai (i.e., 63 teachers) comprising 36 males and 27 females were included. Data collection was carried out by an adapted version of Kayaoglu's (2021) Environmental Literacy Questionnaire and data analysis was conducted via descriptive and inferential statistics with the support of thematic qualitative analysis of the open-ended answers of the teachers. Findings showed that male ECE teachers achieved higher scores on the measures of attitude compared with females, indicating stronger pro-environmental orientations. The qualitative results indicated that although most teachers recognized the importance of environmental issues, there were often more opportunities for male teachers than female teachers, less institutional support and less access to professional training. The study concludes that the environmental attitudes of teachers are affected by gender, opportunities for training, and school culture. Recommendations include targeted professional development programs and gender-sensitive capacity building to facilitate equitable and sustainable practices in environmental education.